'The Little Brother of the Ottoman State': Ottoman technocrats in Kabul and Afghanistan's development in the Ottoman imagination, 1908–23*. (15th April 2016) - O'SULLIVAN, MICHAEL B.
Abstract: By charting the activities of Ottoman experts in Afghanistan from 1908–23, this article demonstrates how their arrival precipitated a series of state-building practices rooted in the particular historical experience of Ottoman reform projects. The country thus became the object of an Ottoman mission civilisatrice and the beneficiary, in the eyes of certain figures within the Ottoman Committee of Union and Progress, of an avowedly Ottoman-Turkish modernity. Sharing this conviction were members of the Afghan royal family and its chief ministers, especially Maḥmūd Ṭarzī, who first invited the Ottoman advisers to Kabul. The provision of Ottoman technical assistance took a variety of forms, but is most evident in military, educational, and public health reforms enacted in Kabul in this period. Through the study of previously unexamined Ottoman, Afghan, and British sources, the aim here is to incorporate these events into discussions of Ottoman informal empire, Afghan developmentalism, and pan-Islam.